2014
DOI: 10.2471/blt.14.135590
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of travel restrictions in the rapid containment of human influenza: a systematic review

Abstract: ObjectiveTo assess the effectiveness of internal and international travel restrictions in the rapid containment of influenza.MethodsWe conducted a systematic review according to the requirements of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Health-care databases and grey literature were searched and screened for records published before May 2014. Data extraction and assessments of risk of bias were undertaken by two researchers independently. Results were synthesized in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
129
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 31 publications
5
129
1
2
Order By: Relevance
“…T Chinazzi et al study the effect of reducing the inflow of infected individuals while simultaneously reducing in the community at large and also find that inflow reduction has only a marginal delay effect unless is reduced drastically (2). These pessimistic findings reflect those from a large number of earlier models (3)(4)(5)(6)(7)(8). The World Health Organization's 2014 Systematic Review on the role of travel restrictions in containing pandemic influenza reviewed 20 23 papers and concluded that a 90% reduction in international air travel would only slow down a pandemic by 3-4 weeks and would not prevent the introduction of a pandemic into any given country (9).…”
Section: Introductionsupporting
confidence: 74%
“…T Chinazzi et al study the effect of reducing the inflow of infected individuals while simultaneously reducing in the community at large and also find that inflow reduction has only a marginal delay effect unless is reduced drastically (2). These pessimistic findings reflect those from a large number of earlier models (3)(4)(5)(6)(7)(8). The World Health Organization's 2014 Systematic Review on the role of travel restrictions in containing pandemic influenza reviewed 20 23 papers and concluded that a 90% reduction in international air travel would only slow down a pandemic by 3-4 weeks and would not prevent the introduction of a pandemic into any given country (9).…”
Section: Introductionsupporting
confidence: 74%
“…No one will be untouched by climate change, but it is not experienced equally. 5 Affluent people can afford to live in insulated buildings with air conditioning and air purifiers. The poor, older people, people with disabilities, and those with pre-existing health conditions are the least able to adapt to the changing climate, unable to escape the fires and heat, and live in dwellings and environments that amplify its effects.…”
Section: Do Not Violate the International Health Regulations During Tmentioning
confidence: 99%
“…1 Many of the travel restrictions being implemented during the COVID-19 outbreak are not supported by science or WHO. Travel restrictions for these kinds of viruses have been challenged by public health researchers, [4][5][6] and WHO has advised against travel restrictions, arguing they cause more harm than good. 7,8 Second, under Article 43.1 any additional health measures implemented by countries "shall not be more restrictive of international traffic and not more invasive or intrusive to persons than reasonably available alternatives".…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Confidence in model accuracy may be increased if multiple different, independent models, developed by independent research groups, converge on a qualitatively similar output (or they may provide clear insight to the reasons for different qualitative behaviour). For example, Mateus and Otete (2014) found that multiple models offer the same qualitative prediction that travel restrictions will not prevent the spread of influenza into susceptible populations. According to Keeling and Rohani (2008), a good model should be both suited to its purpose (as simple as possible but no simpler) and parameterizable by available data.…”
Section: Introductionmentioning
confidence: 99%